OTHR-33. INTRODUCTION OF A MULTIDICIPLINARY NEURO ONCOLOGY LONG TERM FOLLOW UP CLINIC. (3rd June 2022) - Dahl, Christine; Farrell, Nicola; Blount, Nicola; Mould, ryan; Simcox, Angela; Malcolm, Charlotte; Freeman, Anita; King, Vicky; Bell, Daniel; Michalski, Antony; Gan, Hoong-Wei
Abstract: INTRODUCTION: The number of children and young people (CYP) surviving brain tumours is increasing annually with a doubling of 5-year survival over the last 40 years. More than two-thirds of these survivors suffer multiple long-term co-morbidities ("late effects") from their tumour and/ or treatment(s) necessitating lifelong multiprofessional follow-up. This results in multiple appointments and increases the burden of care on patients. Method/Project description To establish a collaborative multidisciplinary "one stop shop" long-term follow-up clinic for CYP >5 years from the end of neuro-oncological treatment to the reduce the need for multiple hospital appointments and to provide holistic assessment and care.The first clinic began in January 2020 as a collaboration between the departments of neuro-oncology, endocrinology, neuropsychology, psychology, physiotherapy and occupational therapy. RESULTS: We have audited the last 60 patients seen in clinic in 2 years and the services they required both in and out of clinic are noted below: Endocrinology – 58 patients Educational help and formal neuropsychology (44 and 39 respectively) There are significant emotional problems in the group and 32 saw clinical psychology and 13 were referred to CAMHS. Physical function issues – 31 saw both physiotherapy and occupational therapy. 10 required referral to orthopaedics Neurology and neurosurgery (13 and 11 respectively) Visual impairment – 33 saw ophthalmology Hearing problems – 17 saw audiology Other organ dysfunction – 4 saw cardiology and 3 urology. We have some feedback data on patient and parent satisfaction with the clinic which shows 92% (13 of 14) families preferred to be seen in the MDT setting rather than by separate clinicians. DISCUSSION: Few models of similar multidisciplinary neuro-oncology long-term follow-up clinics exist in the UK with a lack of streamlined funding, despite recognition from families and professionals about their utility.